2014
DOI: 10.1080/10406638.2014.935449
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in the Snowpack and Surface Water in Blackwood Canyon, Lake Tahoe, CA, as Related to Snowmobile Activity

Abstract: Snowpack in alpine environments may contain appreciable levels of regional pollution acquired through natural processes of wet and dry deposition, as well as from immediate sources such as snowmobile engine exhaust. Understanding the fate and transport of pollutants in alpine environments is a crucial step towards managing emission sources in alpine terrain to mitigate their impacts on natural resources. This study presents detailed chemical analysis for 94 species of polycyclic aromatic hydrocarbons (PAH) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Overall, benzo[a]anthracene, phenanthrene, and 1methylnaphthalene accounted for 68 % of the average PAH profile of these days with known high snowmobile traffic. The predominance of phenanthrene and methylated PAHs in snow samples contaminated by snowmobile emissions has previously being reported (McDaniel and Zielinska, 2014), although the contribution of 2-methylnaphthalene and 2methylfluoranthene in the present study was found to be negligible. Different engine technologies and fuel quality may have been responsible for this.…”
Section: Pah Profilescontrasting
confidence: 50%
See 1 more Smart Citation
“…Overall, benzo[a]anthracene, phenanthrene, and 1methylnaphthalene accounted for 68 % of the average PAH profile of these days with known high snowmobile traffic. The predominance of phenanthrene and methylated PAHs in snow samples contaminated by snowmobile emissions has previously being reported (McDaniel and Zielinska, 2014), although the contribution of 2-methylnaphthalene and 2methylfluoranthene in the present study was found to be negligible. Different engine technologies and fuel quality may have been responsible for this.…”
Section: Pah Profilescontrasting
confidence: 50%
“…No scientific studies on PAC emissions from snowmobiles have been reported yet. Nonetheless, snowmobile driving is a well-documented major source of a list of aromatic hydrocarbons (Zhou et al, 2010;Reimann et al, 2009;Eriksson et al, 2003;Shively et al, 2008), and PAHs were detected in snow along snowmobile tracks (McDaniel and Zielinska, 2014;Rhea et al, 2005;Oanh et al, 2019). Moreover, a factor of 3 higher NO x emissions from snowmobiles compared to gasolinedriven cars in Svalbard are reported by the Norwegian Climate and Pollution Agency (Vestreng et al, 2009) with the main contribution from four-stroke snowmobiles.…”
Section: Nitro-pah Profilesmentioning
confidence: 99%
“…OC compounds that are absorbing in the ultraviolet (UV) and short-visible wavelengths are colloquially known as BrC. The wavelength dependency of BrC aerosol absorption coefficients can be described by an absorption Ångström exponent (AAE) that is significantly greater than one (Chakrabarty et al, 2010;Corr et al, 2012;Kirchstetter et al, 2004;McNaughton et al, 2011;Moosmüller et al, 2011), whereas BC aerosol absorption coefficients are less wavelength-dependent (i.e., AAE ≈ 1) over the visible range and its periphery (Bergstrom et al, 2007;Moosmüller et al, 2009). The optical properties of BrC are described by the wavelength-dependent BrC complex refractive index m λ written as…”
Section: Brown Carbon Aerosolmentioning
confidence: 99%
“…Finally, estimates of basin-wide loading based on spatially extrapolated concentrations and a satellite-based snow water equivalent reconstruction model identify snowpack chemical loading from atmospheric deposition as a substantial source of nutrients and pollutants to the Lake Tahoe Basin, accounting for 113 t of N, 9.3 t of P, and 1.2 kg of Hg each year. McDaniel, 2013;Sickman et al, 2003;TERC, 2011;Vicars and Sickman, 2011;Williams and Melack, 1991a, b). Sierra Nevada snowpack supplies the majority of water to downstream communities as well as to some of the nation's largest agricultural areas.…”
mentioning
confidence: 99%